Self-healing electrolyte for decoupling mechanical strength and conductivity and preparation method of self-healing electrolyte

By introducing hydrogen bond donor and acceptor monomers into the polymer backbone of gel electrolyte and using fluorocyclopropionitrile as solvent, a new self-healing electrolyte was constructed, solving the trade-off between mechanical properties and conductivity, achieving a balance between high mechanical strength and high conductivity, providing a new electrolyte solution for high-performance lithium metal batteries.

CN119812444AActive Publication Date: 2025-04-11HUAZHONG UNIV OF SCI & TECH

Patent Information

Application Number
CN202510233274.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-11
Estimated Expiration
2045-02-28

AI Technical Summary

Technical Problem

While improving mechanical properties, existing gel electrolytes often lead to a decrease in conductivity, making it difficult to balance lithium ion transmission efficiency and mechanical properties.

Method used

A novel self-healing electrolyte is constructed by introducing monomers that provide hydrogen bond donors and acceptors into the polymer backbone and using fluorocyclopropionitrile as a solvent. The polymer backbone of the electrolyte is formed by copolymerization of methacrylamide and methyl methacrylate. The unique structure of fluorocyclopropionitrile can compete for lithium ions and maintain the integrity of hydrogen bonds between polymer segments.

Benefits of technology

The mechanical strength and conductivity of polymer solid electrolytes are decoupled, and self-healing electrolytes with high mechanical strength and high ionic conductivity are provided, providing new electrolyte solutions for the development of high-performance lithium metal batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812444A_ABST
    Figure CN119812444A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and discloses a self-healing electrolyte for decoupling mechanical strength and conductivity and a preparation method thereof. The self-healing electrolyte with the mechanical strength and the conductivity decoupled comprises a polymer skeleton and solvent molecules used for transmitting lithium ions, the polymer skeleton is formed by copolymerizing two monomers, namely methacrylamide for providing a hydrogen bond donor and methyl methacrylate for providing a hydrogen bond acceptor according to a certain proportion in a free radical polymerization manner under the action of an initiator; the solvent molecule is fluorocyclopropionitrile capable of competing for lithium ions on a polymer chain. Before polymerization, a polymer monomer, an initiator and solvent molecules are mixed according to a certain proportion, lithium salt is added, and the solvent molecules are locked in a polymer skeleton in an in-situ polymerization mode. The gel electrolyte provided by the invention has the advantages of high conductivity, high mechanical strength and certain self-healing capability, and can be used for lithium ion batteries and lithium metal batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and more specifically, relates to a self-healing electrolyte with decoupled mechanical strength and electrical conductivity and a preparation method thereof. Background Art

[0002] With the growing demand for high-energy-density batteries in portable electronic devices and electric vehicles, traditional liquid electrolytes can no longer meet the high requirements of modern battery systems for safety, stability, and energy density. Especially for lithium metal batteries, they have great potential in high-energy-density applications, but they also face many challenges, such as the growth of lithium dendrites, compatibility issues between electrolytes and electrode materials, and insufficient ionic conductivity and mechanical properties of the electrolyte itself.

[0003] In the prior art, gel electrolytes are widely used in battery systems to solve the problem of insufficient conductivity of pure solid-state batteries. However, the mechanical properties of gel electrolytes are generally weak, which limits their performance in practical applications. At present, the main methods for improving the mechanical properties of gel electrolytes include introducing cross-linking agents to generate cross-linked polymers and introducing hydrogen bonding functional groups to form hydrogen bonds. However, these methods all have certain limitations. On the one hand, although the increase in the degree of cross-linking can improve the mechanical properties of the polymer, it will lead to an increase in the crystallinity of the polymer, which will significantly reduce the conductivity of the gel electrolyte. On the other hand, although the introduction of hydrogen bonding functional groups can enhance the mechanical properties, it will lead to preferential binding of lithium ions to hydrogen bonding receptors. This will not only reduce the transmission efficiency of lithium ions, but also weaken the enhancement effect of hydrogen bonding on mechanical properties, and also reduce the self-healing ability of the material. Therefore, the existing methods for improving the mechanical properties of gel electrolytes often sacrifice conductivity while improving mechanical properties, and it is difficult to balance the lithium ion transmission efficiency and mechanical properties. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a self-healing electrolyte with decoupled mechanical strength and conductivity and a preparation method thereof, the purpose of which is to develop a gel electrolyte that can provide high mechanical strength and maintain high ionic conductivity, thereby solving the technical problem of insufficient ionic conductivity and mechanical properties of the electrolyte.

[0005] To achieve the above object, according to one aspect of the present invention, a self-healing electrolyte with decoupled mechanical strength and conductivity is provided, comprising a polymer skeleton and solvent molecules for transmitting lithium ions; the polymer skeleton is copolymerized in a certain proportion by free radical polymerization of two monomers, methacrylamide providing a hydrogen bond donor and methyl methacrylate providing a hydrogen bond acceptor, under the action of an initiator; the solvent molecule is fluorocyclopropanenitrile, and its chemical structure is The solvent molecules have a strong attraction for lithium ions, which is beneficial to the desolvation of lithium ions.

[0006] Preferably, the molar ratio of the added amounts of the methacrylamide monomer and the methyl methacrylate monomer is 1:(5-20).

[0007] Preferably, the methacrylamide monomer and the methyl methacrylate monomer are used as polymer monomers, and the added amount of the polymer monomers accounts for 10% to 50% by weight of the self-healing electrolyte.

[0008] Preferably, the initiator is azobisisobutyronitrile.

[0009] Preferably, the initiator addition amount is (0.1-1) wt%, the initiation temperature is 50-80° C., and the polymerization time is 0.5-10 h.

[0010] According to another aspect of the present invention, a method for preparing a self-healing electrolyte with decoupled mechanical strength and conductivity is provided, comprising the following steps:

[0011] S1: preparing a precursor solution: mixing methyl methacrylate, methacrylamide, lithium salt, solvent molecules, and initiator and stirring until the solution is clear;

[0012] S2 drips the precursor solution in S1 onto the separator of the battery and performs drying to obtain a formed self-healing electrolyte.

[0013] Preferably, the lithium salt is one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium hexafluorophosphate, and the amount of the lithium salt added to the self-healing electrolyte is 1 to 5 mol / L.

[0014] Preferably, the specific process of the drying treatment is: placing the assembled battery in an oven at 50 to 80° C. and heating for 0.5 to 10 hours.

[0015] According to another aspect of the present invention, there is provided a lithium secondary battery comprising the self-healing electrolyte described above or the self-healing electrolyte prepared by the method described above.

[0016] In general, compared with the prior art, the above technical solution conceived by the present invention provides a self-healing electrolyte with decoupled mechanical strength and conductivity and a preparation method thereof, which mainly has the following beneficial effects:

[0017] 1. The self-healing electrolyte with decoupled mechanical strength and electrical conductivity proposed in the present invention not only enables the polymer electrolyte to have the combined ability of self-healing, but also solves the trade-off problem between mechanical properties and ionic conductivity of existing polymer solid electrolytes, realizes the decoupling of mechanical strength and electrical conductivity of polymer solid electrolytes, and provides a new electrolyte solution for the development of high-performance lithium metal batteries.

[0018] 2. The present invention proposes a novel molecular structure of a polymer solid electrolyte. By selecting methyl methacrylate with a carbonyl functional group and methacrylamide with an amino functional group as polymer monomers, a novel cross-linked polymer skeleton with abundant hydrogen bonds is constructed, which enables it to have the ability of self-healing.

[0019] 3. The present invention uses fluorocyclopropane nitrile as solvent. The unique structure of this solvent molecule has strong competitiveness for lithium ions, can compete for lithium ions on polymer chains, and prevent lithium ions from occupying hydrogen bonding sites. This characteristic ensures the integrity of hydrogen bonds between polymer segments, and avoids the decline in mechanical properties and self-healing properties caused by the combination of lithium ions with hydrogen bond receptors. In addition, the fluorine atoms in the fluorocyclopropane nitrile molecules can significantly reduce the desolvation energy barrier of lithium ions, thereby promoting the rapid transmission of lithium ions. This design realizes the decoupling of mechanical strength and conductivity of gel electrolytes, and provides new ideas for the design of high-performance battery electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the polymer skeleton molecular structure and solvent molecular structure of the present invention;

[0021] Figure 2 It is a comparison diagram of stress-strain curves of tensile tests of Example 1 of the present invention and Comparative Example 1.

[0022] Figure 3 It is a conductivity test comparison diagram of Example 1 of the present invention and Comparative Example 1.

[0023] Figure 4 It is a comparison chart of the molecular dynamics calculation results of the hydrogen bond quantity of Example 1 of the present invention and Comparative Example 1.

[0024] Figure 5 It is an optical picture showing the self-healing ability of electrolyte Example 1 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0026] See also Figure 1 The embodiment of the present application provides a self-healing electrolyte with decoupled mechanical strength and conductivity, including a polymer skeleton and a solvent molecule for transmitting lithium ions; the polymer skeleton is copolymerized in a certain proportion by free radical polymerization of two monomers, methacrylamide providing a hydrogen bond donor and methyl methacrylate providing a hydrogen bond acceptor, under the action of an initiator; the solvent molecule is fluorocyclopropanenitrile, and its chemical structure is The solvent molecules have a strong attraction for lithium ions, which is beneficial to the desolvation of lithium ions.

[0027] The molar ratio of the added amounts of the methacrylamide monomer and the methyl methacrylate monomer is 1:(5-20).

[0028] Methacrylamide monomer and methyl methacrylate monomer are used as polymer monomers, and the added amount of the polymer monomer accounts for 10% to 50% by weight of the self-healing electrolyte.

[0029] The initiator is azobisisobutyronitrile.

[0030] The added amount of the initiator is (0.1-1) wt%, the initiation temperature is 50-80° C., and the polymerization time is 0.5-10 h.

[0031] The present application also provides a method for preparing a self-healing electrolyte with decoupled mechanical strength and conductivity, comprising the following steps:

[0032] S1: preparing a precursor solution: mixing methyl methacrylate, methacrylamide, lithium salt, solvent molecules, and initiator and stirring until the solution is clear;

[0033] S2 drips the precursor solution in S1 onto the separator of the battery and performs drying to obtain a formed self-healing electrolyte.

[0034] The lithium salt is one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium hexafluorophosphate. The amount of the lithium salt added to the self-healing electrolyte is 1 to 5 mol / L.

[0035] The specific process of the drying treatment is: placing the assembled battery in an oven at 50 to 80° C. and heating for 0.5 to 10 hours.

[0036] Example 1: Preparation of self-healing electrolyte with decoupling of mechanical strength and conductivity

[0037] Weigh 0.2g methacrylamide, 1.8g methyl methacrylate, 0.05g azobisisobutyronitrile, and 1.5g lithium bis(fluorosulfonyl)imide and add them to 6.5g fluorocyclopropanenitrile solvent, stir for 1h to obtain a precursor solution. Keep the precursor solution at 60℃ for 2h to obtain a self-healing electrolyte with decoupling of mechanical strength and conductivity. Then perform the following tests:

[0038] (1) Conductivity test: When assembling a stainless steel-to-stainless steel symmetrical battery, the precursor solution was dripped onto the diaphragm to allow it to soak into the diaphragm. The battery was then assembled and kept warm at 60°C for 2 h. The impedance of the electrolyte was measured using an AC impedance spectroscopy, and its ionic conductivity was calculated based on the conductivity formula.

[0039] (2) Mechanical strength test: The precursor solution was coated on a polytetrafluoroethylene plate and heated at 60°C for 2 h to prepare a self-healing electrolyte with decoupled mechanical strength and conductivity. The electrolyte was subjected to a tensile test using an electronic dynamic and static fatigue testing machine.

[0040] (3) Calculation of hydrogen bond number: Molecular dynamics software is used to calculate the number of hydrogen bonds in the gel electrolyte based on the molecular molar ratio.

[0041] (4) Self-healing test: The precursor solution was coated on a polytetrafluoroethylene plate and heated at 60°C for 2 h to prepare a self-healing electrolyte with decoupled mechanical strength and conductivity. The electrolyte was cut and the fracture surface was kept in contact at room temperature for 10 min to observe the self-healing phenomenon.

[0042] Embodiment 2:

[0043] 0.2 g of methacrylamide, 1.8 g of methyl methacrylate, 0.05 g of azobisisobutyronitrile and 1.5 g of lithium bis(fluorosulfonyl)imide were weighed and added to 6.5 g of cyclopropanenitrile solvent and stirred for 1 h to obtain a precursor solution, which was then tested in the same manner as in Example 1.

[0044] Comparative Example 1:

[0045] Weigh 0.2 g of methacrylamide, 1.8 g of methyl methacrylate, 0.05 g of azobisisobutyronitrile, and 1.5 g of lithium bis(fluorosulfonyl)imide, add to 6.5 g of diethyl carbonate solvent, stir for 1 h to obtain a precursor solution, stir for 1 h to obtain a precursor solution, and test the solution in the same manner as in Example 1.

[0046] See also Figure 2 , is a comparison diagram of stress-strain curves of tensile tests of Example 1 of the present invention and Comparative Example 1; Figure 3 The conductivity test comparison diagram of Example 1 of the present invention and Comparative Example 1; Figure 4 1 is a comparison chart of the molecular dynamics calculation results of the hydrogen bond quantity of Example 1 of the present invention and Comparative Example 1; the performance data test results of each embodiment are shown in Table 1.

[0047] Table 1

[0048]

[0049] Depend on Figure 2-4 As shown in Table 1, in Comparative Example 1, when common diethyl carbonate is used as a solvent, the hydrogen bonding sites are occupied by lithium ions, resulting in low room temperature conductivity and tensile strength of the gel electrolyte, and no self-healing ability. In Example 2, when cyclopropane nitrile with strong lithium ion competitiveness is used as a solvent, the lithium ions occupying the hydrogen bonding sites are released, and the tensile strength and conductivity of the electrolyte are improved, and have a certain self-healing ability. In Example 1, when fluorocyclopropane nitrile is used as a solvent, lithium ions are further released, and the desolvation ability of lithium ions is further enhanced, thereby showing high room temperature conductivity, high tensile strength, and self-healing ability.

[0050] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-healing electrolyte with decoupled mechanical strength and electrical conductivity, characterized in that: The invention comprises a polymer skeleton and a solvent molecule for transmitting lithium ions; the polymer skeleton is copolymerized in a certain proportion by methacrylamide providing a hydrogen bond donor and methyl methacrylate providing a hydrogen bond acceptor under the action of an initiator through free radical polymerization; the solvent molecule is fluorocyclopropanenitrile, and its chemical structure is 2. A self-healing electrolyte with decoupled mechanical strength and electrical conductivity as claimed in claim 1, characterized in that: The molar ratio of the added amounts of the methacrylamide monomer and the methyl methacrylate monomer is 1:(5-20).

3. A self-healing electrolyte with decoupled mechanical strength and conductivity as claimed in claim 1, characterized in that: The methacrylamide monomer and the methyl methacrylate monomer are used as polymer monomers, and the added amount of the polymer monomers accounts for 10% to 50% of the weight percentage of the self-healing electrolyte.

4. A self-healing electrolyte with decoupled mechanical strength and conductivity as claimed in claim 1, characterized in that: The initiator is azobisisobutyronitrile.

5. A self-healing electrolyte with decoupled mechanical strength and conductivity as claimed in claim 4, characterized in that: The added amount of the initiator is (0.1-1) wt%, the initiation temperature is 50-80° C., and the polymerization time is 0.5-10 h.

6. A method for preparing a self-healing electrolyte with decoupled mechanical strength and conductivity as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1: preparing a precursor solution: mixing methyl methacrylate, methacrylamide, lithium salt, solvent molecules, and initiator and stirring until the solution is clear; S2 drips the precursor solution in S1 onto the separator of the battery and performs drying to obtain a formed self-healing electrolyte.

7. The method for preparing a self-healing electrolyte with decoupled mechanical strength and conductivity as claimed in claim 6, characterized in that: The lithium salt is one or more of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium hexafluorophosphate. The amount of the lithium salt added to the self-healing electrolyte is 1 to 5 mol / L.

8. The method for preparing a self-healing electrolyte with decoupled mechanical strength and conductivity as claimed in claim 6, characterized in that: The specific process of the drying treatment is: placing the assembled battery in an oven at 50-80° C. and heating for 0.5-10 hours.

9. A lithium secondary battery, characterized in that: The lithium secondary battery comprises a self-healing electrolyte with decoupling of mechanical strength and electrical conductivity as described in any one of claims 1 to 5, or a self-healing electrolyte with decoupling of mechanical strength and electrical conductivity prepared by the method as described in any one of claims 6 to 8.

Citation Information

Patent Citations

  • Polymer electrolyte, preparation method thereof and application of polymer electrolyte in solid-state battery

    CN114665151A

  • Composite solid electrolyte membrane, preparation method and application thereof, and lithium ion battery

    CN115810792A

  • Viscoelastic conductor polymer electrolyte, preparation method thereof and lithium metal semi-solid-state battery

    CN117154213A

  • Gel electrolyte and preparation method and application thereof

    CN118099516A

  • Deep eutectic gel electrolyte and preparation method and application thereof

    CN119361815A

Cited By

  • Recoverable Turing structure polymer electrolyte as well as preparation method and application thereof

    CN121097199A